2004
DOI: 10.1063/1.1647703
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial characteristics of HfO2 films grown on strained Si0.7Ge0.3 by atomic-layer deposition

Abstract: The interfacial characteristics of gate stack structure of HfO2 dielectrics on strained Si0.7Ge0.3 deposited by atomic-layer deposition were investigated. An interfacial layer including GeOx layers was grown on a SiGe substrate, and the thickness of the GeOx layer at the interfacial layer was decreased after the annealing treatment, while SiO2 layer was increased. The ∼50-Å-thick HfO2 film with an amorphous structure was converted into a polycrystalline structure after rapid annealing at temperature of over 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 13 publications
(9 reference statements)
1
22
0
Order By: Relevance
“…[5][6][7] However, these studies indicate that a relatively high defect density results in poor electrical characteristics, which are caused by interfacial dangling bonds, oxidation states, and oxygen vacancies in HfO 2 /GaAs. Since high defect states at high-j oxides/III-V substrate interface function as electrical traps, high electrical trap density potentially influences the frequency dispersion and device reliability significantly.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] However, these studies indicate that a relatively high defect density results in poor electrical characteristics, which are caused by interfacial dangling bonds, oxidation states, and oxygen vacancies in HfO 2 /GaAs. Since high defect states at high-j oxides/III-V substrate interface function as electrical traps, high electrical trap density potentially influences the frequency dispersion and device reliability significantly.…”
Section: Introductionmentioning
confidence: 99%
“…The coincident energy shift of the oxidized Si peak indicates a net reduction of stoichiometric SiO 2 . Cho et al 17 reported similar findings using XPS to conclude that a layer composed of a mixture of SiO x and GeO x was observed in as-grown HfO 2 films on SiGe and they used medium energy ion scattering (MEIS) to determine from the Ge peak profile and position that Ge is included in the interfacial layer of an SiGe/HfO 2 as-grown sample. 17 They reported that the GeO x layer became significantly reduced with increasing anneal temperature.…”
Section: Methodsmentioning
confidence: 76%
“…Cho et al 17 reported similar findings using XPS to conclude that a layer composed of a mixture of SiO x and GeO x was observed in as-grown HfO 2 films on SiGe and they used medium energy ion scattering (MEIS) to determine from the Ge peak profile and position that Ge is included in the interfacial layer of an SiGe/HfO 2 as-grown sample. 17 They reported that the GeO x layer became significantly reduced with increasing anneal temperature. Our results concur that there is significant Si-O and Ge-O corresponding to the HfO 2 as-dep sample and post 950 C anneal oxidation of bulk Si slightly increases while surface Si slightly decreases.…”
Section: Methodsmentioning
confidence: 76%
“…However, there are many difficulties in realizing Si 1-x Ge x CMOS devices according to different physical and chemical properties of Si 1-x Ge x in comparison with silicon. The most challenging issues that have been widely studied include the structural evolution (SE) of HfO 2 during post-dielectric processes with a large thermal budget [2], the interface instability and VBO between HfO 2 and Si 1-x Ge x [3]. However, the most studies are focused on bulk or thicker (>2nm) HfO 2 .…”
Section: Introductionmentioning
confidence: 99%